PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK MAKET MASJID DAN MAKAM KUNO PENINGGALAN SEJARAH ISLAM DI KOTA JAMBI TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA KELAS X SMA NEGERI 8 KOTA JAMBI - Lopesi, Tri; Azmi, Ulul; Agustiningsih, Nur (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This study aims to determine the effect of the project-based learning model of mosque models and ancient tombs of Islamic historical heritage in Jambi City on the critical thinking skills of class X students of SMA Negeri 8 Jambi City in the 2023/2024 academic year. The research method that is the population in this study is class X students at SMA Negeri 8 Jambi City, the sample used in this study was 72 students. The data collection technique used by the researcher in the research to be carried out is a questionnaire and practice questions. Based on the results of the research that has been carried out on the results of the hypothesis test using the Paired Samples Test, it shows that there is an effect of the project-based learning model of mosque models and ancient tombs of Islamic historical heritage in Jambi City on the Critical Thinking Skills of Class X Students of SMA Negeri 8 Jambi City in the experimental group, as evidenced by the sig. 2 tailed value is smaller than 0.05 (0.002 <0.05), so, the hypothesis that states there is a significant influence between the project-based learning model of mosque models and ancient tombs of Islamic historical heritage in Jambi City on the critical thinking skills of class X students of SMA Negeri 8 Jambi City.